Mutations in the hrp48 gene, which encodes a Drosophila heterogeneous nuclear ribonucleoprotein particle protein, cause lethality and developmental defects and affect P-element third-intron splicing in vivo. - Hammond, L E (1997)
The Drosophila melanogaster hnRNP protein, hrp48, is an abundant heterogeneous nuclear RNA-associated protein. Previous biochemical studies have implicated hrp48 as a component of a ribonucleoprotein complex involved in the regulation of the tissue-specific alternative splicing of the P-element third intron (IVS3). We have taken a genetic approach to analyzing the role of hrp48. Mutations in the hrp48 gene were identified and characterized. hrp48 is an essential gene. Hypomorphic mutations which reduce the level of hrp48 protein display developmental defects, including reduced numbers of ommatidia in the eye and morphological bristle abnormalities. Using a P-element third-intron reporter transgene, we found that reduced levels of hrp48 partially relieve IVS3 splicing inhibition in somatic cells. This is the first direct evidence that hrp48 plays a functional role in IVS3 splicing inhibition.